Collaborating With Parks and Recreation Departments to Address Youth Health - Risisky, Deb; MacGregor, James (Health Promotion Practice, 2021)
Adolescence is an important time for addressing health, including mental health, obesity, substance use, and food insecurity. As the myriad health and wellness needs of community members expands, it becomes increasingly difficult for one profession alone to address these needs. The park and recreation field was founded to address the health and wellness needs of people, and much of their programming is focused on youth. Thus, municipal park and recreation departments are becoming increasingly involved in collaborative partnerships with other health-serving agencies within their community. This study explored park and recreation directors’ experiences in collaborating with health agencies to better address health and wellness factors that affect the youth in their communities. This phenomenological qualitative study employed in-depth interviews with park and recreation directors and used thematic analysis. Nine interviews were conducted from four of the six New England states. The most common health concern seen by the directors was mental health, primarily behavioral health challenges. Parks and recreation collaboration with public health organizations ranged from none to close collaborations; directors regularly spoke about wanting to strengthen their collaborations. Public health and park and recreation staff have similar challenges with staffing and resources; additionally, they have complimentary skills with regard to planning and implementing health-related programs. For that reason, creating purposeful collaborative partnerships between public health agencies and park and recreation departments, focused on measurable outcomes, may increase benefits to the health of youth in a community.
Keywords: adolescent health; collaboration; dept.pch; dept.rec; mental health; multisector; park and recreation; peer-reviewed; physical activity; prevention; trauma

Post-Graduation Impact of a Program Planning Service-Learning Project. - Risisky, Deb; Goldson, Tess; DeMezzo, Robert (Pedagog. health promot., 2020)
Research has shown that service-learning can increase student-learning outcomes across various disciplines. Service-learning opportunities have been steadily increasing in college settings, especially in health-related fields. This evaluation of an undergraduate public health course at a mid-size, public university in New England sought to understand the impact of service-learning on material retention, internships, and post-graduation public health careers. A 25-item questionnaire was emailed to students who took the course between the Fall 2010 and Spring 2016 semesters with 75 completed (33.3% completion rate). More than half of the respondents noted that their participation in a service-learning project positively affected their internship experience, their first post-graduation job, and their overall career, while also helping them retain the course material after graduation. Open-ended responses provided insight to the qualitative responses. Respondents noted that in addition to having the understanding and ability to put on programs in their community, they also had more confidence in their abilities. The opportunity to practice public speaking skills as well as work collaboratively in group settings, were both noted as essential skills needed to succeed in the public health workforce. It was concluded the project had a positive impact on student's learning and retention in planning, implementing, and evaluating an actual health promotion program as well as how they were able to use those skills in their careers., (C)2021Sage Publications
Keywords: dept.fye; dept.pch; dept.rslf; health education; peer-reviewed; program planning; service-learning

Health Information Access Behaviors by Sexual Orientation: A Secondary Data Analysis of the National Health Interview Survey - Gagnon, Kelly; Corey, Stephanie; Gordon, Jacob; Risisky, Deb; Coulter, Robert (Journal of Homosexuality, 2025)
Sexual minority (SM) adults are at increased risk for adverse health outcomes and face unique barriers to engagement and retention in healthcare, including stigma and discrimination. Given known barriers to care, SM adults may prefer online platforms due to limited access to in-person clinical care and fear of discrimination. To date, there is limited knowledge of these behaviors among subgroups of SM adults. This study was a cross-sectional, secondary data analysis of the United States National Health Interview Survey (NHIS) Adult Sample Data Set, 2018. Utilizing descriptive statistics and multivariable logistic regressions, we found that bisexual females had significantly greater odds (AOR = 1.58, CI: 1.04-2.39) of seeking health information online compared to straight females. Similarly, when compared to their straight male counterparts, gay males had significantly higher odds of seeking health information online in the past 12 months (AOR = 2.96, 95% CI: 2.00-4.37). These findings indicate the need for targeting messaging and interventions to address the health concerns of these populations. It also suggests that virtual platforms are viable and perhaps preferred for these subgroups of SM adults. Through continued efforts and research, the field can target relevant health information to populations who need it most by leveraging where they seek it.
Keywords: Environmental health; Health Information National Trends Survey; Health care; Health information; Homosexuality; Medicine; National Health Interview Survey; Orientation (vector space); Political science; Psychology; Reproductive health; Sexual behavior; Sexual minority; Sexual minority health; Sexual orientation; Social psychology; Survey data collection; bisexual women; dept.pch; gay men; health information access; healthcare utilization; online health information; peer-reviewed; public health

Promoting pro-social skills to reduce violence among urban middle school youth - Risisky, Deb; MacGregor, J; Smith, D. A.; Abraham, J; Archambault, M (Journal of Youth Development, 2019)
Adolescent violence is a significant public health problem. The goal of this evaluation was to determine whether communication skills, relationships with adults, and relationships with peers were enhanced through participating in an after-school program aimed at reducing violence-related behaviors among urban middle school youth. Elements that helped to foster success among our population were providing a program that enabled consistent choice in recreational activities in a safe place, and also providing busing home to increase safety. A non-experimental study was conducted with 115 students who participated in the program. Bivariate, ANOVA analysis, and Kruskal–Wallis tests were carried out. Results indicated that participating in the program significantly impacted student relationships with adults and their peers as well as positively impacted their communication skills. The program was designed with purposeful activities that would address pro-social behaviors, enhance youth interest, and increase attendance. The program specifically used recreation to help foster relationships with their peers and the adults in the program, with the intention of reducing conflict, and therefore violence among the students.
Keywords: After-school program; Recreation programs; Youth violence; dept.pch; dept.rec; peer-reviewed

Utilizing Local Professional Association Chapters as Pathways for Leadership Development - Batista, Nicole; Risisky, Deb; Lutz, Tara M.; Clinesmith, Ellen; Morgan, Jahkeeva (Health Promotion Practice, 2024)
In 2019, there was no entity specifically dedicated to health promotion and education practitioners in Connecticut or New England. This made it difficult for health promotion practitioners and students to network, collaborate, and engage in professional development. The purpose of this article is to share our experiences developing the new Connecticut Chapter of the Society for Public Health Education (CT SOPHE), including how we leveraged student interns during the first two years to promote organizational growth. To build our membership, it was important to determine who would be interested in joining CT SOPHE and so we focused on three groups: the current workforce/professionals, future workforce/students, and future leaders/interns. Over the course of these two years, three interns were recruited to help with creating a needs assessment (MPH student) and program development (two BS students); the organization was established by an MPH student as her internship project. Three former interns share how their experience working with the CT SOPHE board has helped them develop crucial leadership skills early in their careers. Embedding student interns into the framework and operations of CT SOPHE demonstrates an intentional and strategic commitment to the sustainability of both the organization and the workforce.
Keywords: dept.pch; peer-reviewed

Examining Delivery Method and Infant Feeding Intentions between Women in Traditional and Non-Traditional Prenatal Care. - Risisky, Deb; Chan, Ronna L; Zigmont, Victoria A; Asghar, Syed Masood; DeGennaro, Nancy (Maternal and child health journal, 2018)
Introduction The purpose of the study is to evaluate delivery method and breastfeeding initiation in women enrolled in group prenatal care (CenteringPregnancy) and in traditional prenatal care. Methods Data were obtained from medical records of a hospital-based midwifery practice in south central Connecticut that offered both types of prenatal care programs. Medical information from 307 women enrolled in this practice was included in the analysis. Out of the 307, 80 were enrolled in group prenatal care. Socio-demographic, lifestyle, and previous and current obstetrical information from medical records formed the basis of comparison. Bivariate and logistic regression analyses were carried out. Results Women in Centering had fewer planned cesarean sections (1.3 vs. 12.8%) and had a higher breastfeeding initiation (88.7 vs. 80.0%). However, Centering women were found to have a higher portion of unplanned cesarean sections (27.5 vs. 11.0%). Both the unadjusted and the adjusted odds ratios of having a cesarean planned delivery were lower in the group care. Women in Centering had 2.44 (95% CI 1.05, 5.66) times the odds of breastfeeding initiation compared to the odds for women in traditional prenatal care after adjusting for maternal age, smoking status, gestation and race. Discussion CenteringPregnancy can have positive impact for the woman and baby. This program implementation saw lower rates of elective cesarean sections and increased breastfeeding compared to women in traditional care.
Keywords: *Breast Feeding/px [Psychology]; *Breast Feeding/sn [Statistics & Numerical Data]; *Cesarean Section/sn [Statistics & Numerical Data]; *Intention; *Mothers; *Prenatal Care/mt [Methods]; Adult; Breast Feeding; Breastfeeding; CenteringPregnancy; Cesarean Section; Cesarean section; Connecticut; Female; Group Processes; Humans; Infant; Infant, Newborn; Intention; Mothers; Mothers/px [Psychology]; Mothers/sn [Statistics & Numerical Data]; Pregnancy; Prenatal Care; Prenatal care; Standard of Care; adult; behavior; breast feeding; cesarean section; comparative study; dept.pch; female; group process; health care quality; human; infant; mother; newborn; peer-reviewed; pregnancy; prenatal care; procedures; psychology; statistics and numerical data